Reconstruction of Electronic Deed Regulations Based on Legal Certainty and Justice in the Indonesian Notary System - Marsella Marsella; Rafiqi Rafiqi (Civiliza Publishing, 2026)
The transformation of information technology has driven the digitalization of notarial services, including the growing use of electronic deeds in various legal transactions. However, the regulation of electronic deeds in Indonesia still raises legal certainty issues due to the lack of integration of provisions in the Notary Law with the Electronic Information and Transactions Law. This study aims to examine the regulation of electronic deeds, assess their evidentiary strength, and formulate a regulatory reconstruction model based on legal certainty and justice. The study uses normative legal methods with a statutory, conceptual, and case approach, through a qualitative analysis of primary, secondary, and tertiary legal materials. The results of the study indicate that the regulation of electronic deeds is still scattered and does not clearly regulate the form, procedures for making, and the status of evidence. Therefore, regulatory harmonization, explicit recognition of electronic deeds as authentic deeds under certain conditions, implementation of digital security standards, and affirmation of notary responsibilities are needed to create legal protection and justice for the parties.